Mitigasi Bencana Berbasis Masjid: Studi Kasus Pengalaman Masyarakat di Wilayah Rawan Bencana Yogyakarta - Napsiah Napsiah; Marfuah Sri Sanityastuti (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
Indonesia is highly vulnerable to natural disasters, particularly earthquakes and tsunamis, which often cause significant social and physical impacts. This study aims to examine the role of mosques in disaster mitigation through a case study of community experiences in disaster-prone areas of Yogyakarta. A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews. The quantitative data were collected from 204 households to assess disaster awareness, while qualitative data explored the mitigation practices centered around the mosque. The findings reveal that 94% of respondents know they live in disaster-prone areas, and 91% stated they would evacuate to the mosque during a disaster. The mosque functions as a place of worship and as a structurally resilient evacuation center equipped with disaster-related infrastructure and early warning systems. This study highlights the significant role of mosques in strengthening community preparedness and suggests that such religious-social institutions can serve as effective models for localized disaster mitigation strategies.